Quantitative, Label-Free Characterization of Stem Cell Differentiation at the Single-Cell Level by Broadband Coherent Anti-Stokes Raman Scattering Microscopy - Lee, Young Jong (Mary Ann Liebert, Inc., 2014)
We use broadband coherent anti-Stokes Raman scattering (BCARS) microscopy to characterize lineage commitment of individual human mesenchymal stem cells cultured in adipogenic, osteogenic, and basal culture media. We treat hyperspectral images obtained by BCARS in two independent ways, obtaining robust metrics for differentiation. In one approach, pixel counts corresponding to functional markers, lipids, and minerals, are used to classify individual cells as belonging to one of the three lineage groups: adipocytes, osteoblasts, and undifferentiated stem cells. In the second approach, we use multivariate analysis of Raman spectra averaged exclusively over cytosol regions of individual cells to classify the cells into the same three groups, with consistent results. The exceptionally high speed of spectral imaging with BCARS allows us to chemically map a large number of cells with high spatial resolution, revealing not only the phenotype of individual cells, but also population heterogeneity in the degree of phenotype commitment.